Quasi-static compression behaviour of interlocking core structures made of flax fibre reinforced polylactic acid composite - Alsubari, S.; Zuhri, M.Y.M.; Sapuan, S.M.; Ishak, M.R. (Elsevier, 2020)
Natural fibres have been gaining a lot of attention for its use in various of fields. It has a potential to replace synthetic fibre due to their availability from renewable natural resources, high specific strength and modulus, low cost, light weight and biodegradability. This paper investigates tensile and quasi static compression properties of flax reinforced polylactide acid (flax/PLA) composites. Initially, the effect of variation of manufacturing temperature on tensile properties of flax PLA composites was examined at three different temperatures of 170, 180 and 190 °C a pressing times of 5, 10 and 15 min were considered. Then a range of double cell walls interlocking square core structures were manufactured using hot press machine and later fabricated through a simple slotting technique. Next, the sandwich structures were tested under quasi-static compression loading with a crosshead displacement rate of 2 mm/min to evaluate their compression properties. The study revealed that that flax/PLA composites manufactured at a temperature of 180℃ and pressed for 5 min. gave the highest value of strength, whereas a temperature of 190℃, pressed for 15 min. is the lowest. Furthermore, results showed that sandwich structures with double cell walls exhibited better strength and energy absorption capacity by approximately 80 and 86% respectively than those offered by ingle cell wall cores as reported in the literatures.